Emerging Mechanisms of Growth and Patterning Regulation by Dachsous and Fat Protocadherins - Gridnev, Artem; Misra, Jyoti R. (Frontiers in Cell and Developmental Biology, 2022)
Fat and Dachsous are evolutionarily conserved cell adhesion molecules that play a critical role in development of multiple organ systems. Much of our understanding of this signaling pathway comes from studies from Drosophila, where they initiate a signaling pathway that regulate growth by influencing Hippo signaling and morphogenesis by regulating Planar Cell Polarity (PCP). In this review, we discuss recent advances in our understanding of the mechanisms by which this signaling pathway regulates these developmental processes. Further, we discuss the progress in understanding how they function in mammals.